The effect of health education in improving the knowledge and attitudes of integrated service post cadres about early detection of high‑risk pregnancies in the working area of the Mamajang health center, Makassar city, Indonesia - Ayu B. Fauziah; Apik I. Moedjiono; Masni Masni; Arifin Seweng; Sukri Sukri; Healthy Hidayanty (AOSIS, 2023)
Maternal mortality can be reduced by strengthening the process of early detection of high-risk pregnancies. However, the lack of knowledge related to high-risk pregnancy is still an obstacle. This study aims to analyze the effect of health education on the knowledge and attitudes of cadres about early detection of high-risk pregnancy in the working area of Health Centre Mamajang Makassar City. Experimental research with a pretest protest design with a control group, involving 80 cadres spread across 20 Integrated Service Posts who were divided into four treatment groups. There was an increase in mean knowledge between the intervention group (P=0.000) and the control group (P=0.002). There was also an increase in attitude between the intervention group (P=0.000). However, there was no improvement in attitude (P=0.475) in the control group. The intervention group through combined video+booklet had the highest mean knowledge score (6.65-13.90) than the groups that received intervention through video (6.60-12.69) or booklet alone (6.75-12.07), respectively. On attitude, the highest average attitude score in the intervention group was the combined video+booklet group (22.0-35.8), video (21.22-34.65) and booklet alone (22.25-34.55). While the average score of the control group on knowledge (6.00-6.95) and attitude (22.60-23.05). The role of health education by involving a combination of both video and booklet media is appropriate as an effort to influence Integrated Service Post cadres in increasing knowledge and attitudes about the early detection of high-risk pregnancies